Kemampuan Konseptual dan Prosedural dalam Menyelesaikan Soal Cerita Volume Kubus dan Balok - Nurjanah, Vivi Fauzia; Isrokatun, Isrokatun; Irawati, Riana (Jurnal Pena Ilmiah, 2019)
This research is a descriptive study that will describe about the conceptual ability of cube to solve cube volume’s story matter, conceptual ability of beam to solve  beam volume’s story matter, and procedural abilities to solve  cube and beam volume’s story matter. The existence of this study is itended to be basis in decide a solution to solve the problem of story matter especially in cube and beam volume materials. This research used descriptive method with diagnostic test instrument, interview, and field notes. The result of this study showed that the student’s conceptual abilities of cube were classified as very low, the student’s conceptual abilities of beam were classified as very low, and the student’s procedural abilities were classified as very low too.